2021
DOI: 10.3390/cells10081892
|View full text |Cite
|
Sign up to set email alerts
|

Role of Long Non-Coding RNAs in Pulmonary Arterial Hypertension

Abstract: Pulmonary arterial hypertension (PAH) is a debilitating condition of the pulmonary circulatory system that occurs in patients of all ages and if untreated, eventually leads to right heart failure and death. Despite existing medical treatment options that improve survival and quality of life, the disease remains incurable. Thus, there is an urgent need to develop novel therapies to treat this disease. Emerging evidence suggests that long non-coding RNAs (lncRNAs) play critical roles in pulmonary vascular remode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 107 publications
0
16
0
Order By: Relevance
“…They are mainly located in the nucleus of the cell, along with a low level of expression. They play an important epigenetic role by functioning as suppressors or activators of gene transcription and mRNA translation, miRNA precursors, RNA stabilizers, and sponges [ 165 ]. Emerging evidence has demonstrated a link between lncRNAs and the initiation of various human diseases, including cancer and cardiovascular and neurodegenerative diseases [ 165 ].…”
Section: Epigenetic Mechanisms Of Pathogenesis In Pahmentioning
confidence: 99%
See 2 more Smart Citations
“…They are mainly located in the nucleus of the cell, along with a low level of expression. They play an important epigenetic role by functioning as suppressors or activators of gene transcription and mRNA translation, miRNA precursors, RNA stabilizers, and sponges [ 165 ]. Emerging evidence has demonstrated a link between lncRNAs and the initiation of various human diseases, including cancer and cardiovascular and neurodegenerative diseases [ 165 ].…”
Section: Epigenetic Mechanisms Of Pathogenesis In Pahmentioning
confidence: 99%
“…They play an important epigenetic role by functioning as suppressors or activators of gene transcription and mRNA translation, miRNA precursors, RNA stabilizers, and sponges [ 165 ]. Emerging evidence has demonstrated a link between lncRNAs and the initiation of various human diseases, including cancer and cardiovascular and neurodegenerative diseases [ 165 ]. Pathological changes of PAH include excessive cell proliferation, migration, and a loss of balance between cell growth and death induced by apoptosis.…”
Section: Epigenetic Mechanisms Of Pathogenesis In Pahmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that lncRNAs such as H19, TYKRIL, MEG3, MANTIS and HOXA-AS3 play major role in PH development and progression [5].…”
mentioning
confidence: 99%
“…Considering the pivotal role of lncRNAs in regulating various biological processes, lncRNA-based therapies represent a promising therapeutic approach, especially for diseases with poor treatment options, such as PH. Several studies have shown that lncRNAs, such as H19, TYKRIL, MEG3, MANTIS, and HOXA-AS3, play a major role in PH development and progression ( 5 ).…”
mentioning
confidence: 99%